Awaken your genius : escape conformity, ignite creativity, and become extraordinary - Varol, Ozan O., 1981- (PublicAffairs, 2023)
"From the critically acclaimed author of Think Like a Rocket Scientist comes a simple process for discarding obsolete beliefs and cultivating independent thought A rare handful of leaders, artists, scientists, and entrepreneurs seem to have Teflon in their heads. They think and act with genuine independence, offering up ideas and insights direct from the subtle workings of their own minds. No matter how far that might take them from their social or political group. We sometimes call these people geniuses, as if they're another breed. But genius doesn't have to belong to just a few people-it can be cultivated. Great thinkers operate unconstrained by the opinions of others-or their own past opinions. They can act on new information regardless of the beliefs they once held, or identities they once adopted. They distinguish fact from manipulation. And just as importantly, they act first instead of reacting-creating new ideas and opportunities for themselves and others. This is a book for aspiring universe-denters: executives and entrepreneurs, activists and artists, individuals who want to escape groupthink, discard obsolete and harmful beliefs, generate breakthrough ideas, spot hidden opportunities, and flourish in a world of ever-increasing manipulation, change, and challenge. In short, it's a book for geniuses"--